ONE STANDARD CONVOLUTION IDENTITY - Movsisian, A. M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
In this paper one standard convolution identity of vector space is considered. This identity can be presented as a determinant of operators.